PENATAGUNAAN LAHAN REKLAMASI DAN REVEGETASI PADA KEGIATAN PENAMBANGAN BIJIH NIKEL PT IFISHDECO TBK KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - La Ode Miqdad Husein (Retii, 2021)
In good use of ex-mining land, it is necessary to apply good and correct reclamation so that it can realize environmentally sound development. The purpose of this study was to examine the stages of the land use management process for reclamation and revegetation carried out by PT Ifishdeco with research methods directly involved in daily research activities. PT Ifishdeco manages the reclamation land use with a land area of 202.67 Ha which is divided into 97.29 Ha North Block and 105.38 Ha South Block. PT Ifishdeco carries out reclamation activities through the stages of planning, land preparation, land management, nurseries, planting and maintenance and monitoring. The types of plants used were legumes (Arachis hypogaea L.) as cover crops, cassava (Manihot esculenta) as pioneer plants and cashew nuts (Anacardium occidentale) and gamal (Gliricidia sepium) as core plants.